ANALISIS FAKTOR FISIKA PENYEBAB KERUSAKAN KOLEKSI CETAK DI PERPUSTAKAAN UMUM KABUPATEN MALANG - Ratri Noor Wulandari, Eka; Mega Asri, Tri; Faris Naufal, Muhammad (BACA: Jurnal Dokumentasi dan Informasi, 2020)
The majority of library materials are in printed form. The printed collection generally made of cellulose paper which is influenced by various factors. The physical factor is a factor that affects the damage of library materials such as temperature, humidity, light, and dust. Public Library of Malang Regency is a library that has printed collection of more than 25.000 copies and most of it is in damaged condition. The damage in the collection such as dusty, moldy, and crumpled conditions. In this experiment, light and dust were observed in the library room and collection. Furthermore, temperature and humidity were measured by a thermohygrometer. Based on the experimental result obtained that dust attach both in collection and bookshelf. The source of light in the library comes from sunshine and lamp. The daily temperature average in this library is 27.4oC and the humidity is 65%RH. This value is higher than the required condition which is temperature of 19°C-23°C and humidity of 40-50%RH.